Nickel Tetrasulfonated Phthalocyanine Decorated with AuNP as a Double Sensorial Platform: SERS and Electrochemical - Martin, Cibely Silva [UNESP]; Kavazoi, Henry Seitiro [UNESP]; Miyazaki, Celina Massumi [UNESP]; Alessio, Priscila [UNESP]; Constantino, Carlos José Leopoldo [UNESP] (MDPI, 2023)
The development of materials for multiple applications is a challenge in the fields of technology and materials science. In this work, screen-printed carbon electrodes (SPCEs) were modified with an electropolymerized nickel tetrasulfonated phthalocyanine film (polymeric-NiTsPc = p-NiTsPc) decorated with gold nanoparticles (AuNP). The modified SPCEs were applied as a sensing platform for analysis via electrochemical and surface-enhanced Raman scattering (SERS) spectroscopy. The SPCEs modification was based on the potential cycling firstly in a NiTsPc solution and then in an AuHCl4 solution, with the fast formation of spherical AuNP through the p-NiTsPc film surface. The modified electrode based on SPCE/p-NiTsPc/AuNP showed a synergetic effect in voltammetric measurements in [Fe(CN)6]3−/[Fe(CN)6]4− probe as well as an electrocatalytic effect in the presence of dopamine. The calibration curve towards dopamine detection presented a linear range from 1 to 10 μmol/L with a limit of detection of 0.73 μmol/L. The spectroelectrochemistry measurements combining SERS and the applied potential of −60 mV showed that the SPCE/p-NiTsPc/AuNP and SPCE/AuNP can be powerfully used as a dual sensing platform for dopamine detection. In the case of SPCE/p-NiTsPc/AuNP, p-NiTsPc plays an important role in facilitating electron transfer during the electrochemical reaction, while AuNP is crucial for obtaining SERS signals for dopamine detection.
Keywords: dopamine; electrodeposition; gold nanoparticles; NiTsPc; SERS; spectroelectrochemical